2017
DOI: 10.2147/copd.s130616
|View full text |Cite
|
Sign up to set email alerts
|

Expression profiling of miRNA-145 and miRNA-338 in serum and sputum of patients with COPD, asthma, and asthma–COPD overlap syndrome phenotype

Abstract: Background and objectivesA new phenotype with overlapping characteristics between asthma and chronic obstructive pulmonary disease (COPD) called asthma–COPD overlap syndrome (ACOS) is emerging among inflammation diseases. To date, there is no agreement on specific criteria to define this syndrome, and the current guidelines are insufficient to classify the analogy and differences between overlap and COPD or asthma phenotypes. It would be necessary to identify new biomarkers able to identify these diseases clea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
57
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 69 publications
(58 citation statements)
references
References 29 publications
1
57
0
Order By: Relevance
“…[6][7][8] Nevertheless, the field of miRNAs as biomarkers for these diseases is still scarce, since it has only been described that COPD, ACO and asthma show higher sputum levels of miR-145 and miR-338 compared with healthy subjects. 9 Here, we show that serum miRNAs are promising biomarkers of respiratory diseases, with high values of sensitivity and specificity. We previously described a specific miRNAs profile that was upregulated in asthma compared with healthy controls.…”
Section: Until Now Several Biomarkers Have Been Investigated In Asthmamentioning
confidence: 73%
“…[6][7][8] Nevertheless, the field of miRNAs as biomarkers for these diseases is still scarce, since it has only been described that COPD, ACO and asthma show higher sputum levels of miR-145 and miR-338 compared with healthy subjects. 9 Here, we show that serum miRNAs are promising biomarkers of respiratory diseases, with high values of sensitivity and specificity. We previously described a specific miRNAs profile that was upregulated in asthma compared with healthy controls.…”
Section: Until Now Several Biomarkers Have Been Investigated In Asthmamentioning
confidence: 73%
“…Previous studies have indicated that circulating miRNAs possess diagnostic value and suitability for the detection of tumors (12,14). For instance, the abnormal expression of miRNA-145 and miRNA-338 was identified in serum and sputum samples of patients with chronic obstructive pulmonary disease and asthma (15). In addition, decreased miR-433 and miR-133b levels in the blood may predict the progression of Parkinson's disease (16).…”
Section: Introductionmentioning
confidence: 99%
“…9 In addition to the key genes related to COPD pathogenesis, non-coding RNAs containing microRNAs (miRNAs) have been shown to be concerned with COPD. 10,11 miRNAs, with [19][20][21][22][23][24][25] nucleotides, are a series of small endogenous nucleotide RNAs that participate in various biological processes by negatively modulate genes expression under post-transcriptional level. 12,13 The dysregulation of miRNAs are involved in multifarious diseases including COPD, which are often utilized as biomarkers for exposure to environmental factors.…”
Section: Introductionmentioning
confidence: 99%